Organized Crime and Electoral Outcomes in Sicily - Paolo Buonanno; Giovanni Prarolo; Paolo Vanin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This paper investigates the relationship between mafia and politics by focusing on the market for votes. It exploits the fact that in the early 1990s the Italian party system collapsed, new parties emerged and mafia families had to look for new political allies. It presents evidence, based on disaggregated data from the Italian region of Sicily, that between 1994 and 2008 Silvio Berlusconi's party, Forza Italia, obtained higher vote shares in municipalities plagued by mafia. The result is robust to the use of different measures of mafia presence, both contemporary and historical, to the inclusion of different sets of controls and to spatial analysis. Instrumenting mafia's presence by determinants of its early diffusion in the late XIX century suggests that the correlation reflects a causal link, which would be coherent with mafia's choice to back Forza Italia in exchange for favorable policies.
Keywords: D72; K42; 330